EFEKTIFITAS PENGGUNAAN MEDIA TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM KEMAMPUAN MENYUSUN KALIMAT PADA ANAK TUNARUNGU DI SLB TANJUNGPINANG. - Riasnelly - Riasnelly (Jurnal Penelitian Pendidikan Khusus, 2013)
The research was motivated by the inability of deaf children in developing structured sentences, so the intent and meaning of the sentence that made ​​it difficult to understand by others, which in turn inhibits the deaf child's communication. Therefore, the author tries to use information and communication technology as a medium of learning the Indonesian language in deaf children to help improve ability to construct a sentence is structured. Formulation of the problem in this research is "How can the effectiveness of media use Information and Communication Technology (ICT) in the ability to construct a sentence in deaf children? '. The population in this study were students deaf high school level Extraordinary Tanjungpinang and total sample amounted to 5 students with hearing impairment. The method used in this study is an experimental method with the "One Group Pre-test and Post-test". Data collection techniques used were written tests, while data analysis techniques using Wilcoxon test. Indonesian language learning using information technology and communication media is more effective in learning Indonesian about making the sentence structure, faster students know about the word as the subject, predicate, object, and a description of where and how to make a sentence structured and patterned. This is because, in the information technology and communication media is placing more emphasis on the regularity of the word in a sentence, so that the misplacement of words or phrases that are often created confusion deaf children is not the case. Based on the results of this study should be a consideration for schools and teachers SLB-B in providing learning Indonesian language media information and communications technology to enhance the ability to make the sentence structure in children with hearing impairment.